Individual differences in risky decision-making among seniors reflect increased reward sensitivity - James F eCavanagh; James F eCavanagh; David eNeville; Michael X Cohen; Irene eVan de Vijver; Helga A Harsay; Andrea eWatson; Jessika I V Buitenweg; K. Richard eRidderinkhof; K. Richard eRidderinkhof (Frontiers in Neuroscience, 2012)
Increasing age is associated with subtle but meaningful changes in decision-making. It is unknown, however, to what degree these psychological changes are reflective of age-related changes in decision quality. Here, we investigated the effect of age on latent cognitive processes associated with risky decision-making on the Balloon Analogue Risk Task (BART). In the BART, participants repetitively inflate a balloon in order to increase potential reward. At any point, participants can decide to cash out to harvest the reward, or they can continue, risking a balloon pop that erases all earnings. We found that among seniors, increasing age was associated with greater reward-related risk taking when the balloon has a higher probability of popping (i.e., a high risk condition). Cognitive modeling results from hierarchical Bayesian estimation suggested that performance differences were due to increased reward sensitivity in high risk conditions in seniors.